INDONESIAN STUDENTS’ STRATEGIES TO COPE WITH FOREIGN LANGUAGE ANXIETY - Abdurahman, Nur Hafiz; Rizqi, Muhammad Ainur (TEFLIN Journal, 2020)
Previous research reports that foreign language anxiety (FLA) is one of the affective factors exerting influence on foreign language learning. Myriad studies have examined how foreign language learners cope with foreign language anxiety. However, few studies have addressed the particular moments when students feel the most anxious and how they cope with this anxiety. The present study aims to (1) identify specific moments when students feel the most anxious; (2) investigate their coping strategies, and (3) recognize the changes in the strategies used by the students during specific moments in their language learning. In so doing, a stimulated recall was carried out among five university students from non-English departments who had to conduct presentations in English. The findings show that they displayed different levels of anxiety, which resulted in several accidents during the presentation. The participants with a high anxiety level tended to utilize monotonous coping strategies. This study implies that teachers need to take into account their students’ anxiety levels before they commence a new term or semester. When encountering highly anxious students, they can introduce the learners to alternative strategies to cope with anxiety.